2014
DOI: 10.20884/1.sb.2014.1.3.42
|View full text |Cite
|
Sign up to set email alerts
|

Aktivitas Superoksida Dismutase Tikus Diabetes Yang Diberi Ekstrak Batang Kapulaga Dan Glibenklamid

Abstract: A B S T R A C TSuperoxide Dismutase (SOD) is an antioxidant enzyme which reduce anion superoxide radicals as well as known caused of diabetes. There are many natural additive was believed having capacity to repaired an antioxidant celluler status. Cardamom's stem were repor ted containing flavonoid and vitamin C which have been proven as in vitro antioxidant. There was no data showing its in vivo potency. This study aims to knoe the SOD activity of diabetes rats which were given cardamom stem extract (CSE) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
(15 reference statements)
0
7
0
1
Order By: Relevance
“…Cu 2+ and Zn 2+ are required as enzyme stabilizers. SOD function to accelerate O2 dismutation and maintain balance between the amount of O2 and H2O2 formation (Rahmawati et al 2014). The result of SOD activity measurement showed that SNEDDS ginger extract with eel fish oil at the same dose with pure ginger extract has higher SOD activity.…”
Section: Discussionmentioning
confidence: 99%
“…Cu 2+ and Zn 2+ are required as enzyme stabilizers. SOD function to accelerate O2 dismutation and maintain balance between the amount of O2 and H2O2 formation (Rahmawati et al 2014). The result of SOD activity measurement showed that SNEDDS ginger extract with eel fish oil at the same dose with pure ginger extract has higher SOD activity.…”
Section: Discussionmentioning
confidence: 99%
“…A preliminary phytochemical analysis of the EESL was shown flavonoids, steroids/triterpenoids, tannins, glycosides and saponins. Flavonoids, their glycosides and saponins are responsible for blood glucose decreasing activity through increased insulin secretion, as shown in an experiment by NA-STZ induced diabetic rats, which is capable of stimulating pancreatic secretion [10], [11].…”
Section: Discussionmentioning
confidence: 99%
“…According to Rahmawati et al (2014), vitamin C helps in reducing the amount of superoxide anion radicals and increasing SOD activity by inhibiting the protein glycation process. In addition, vitamin C can act as an exogenous antioxidant which can substitute the role of endogenous antioxidants if they are low in the body.…”
Section: Resultsmentioning
confidence: 99%